PENGUATAN KARAKTER USIA DASAR BERBASIS PEMBELAJARAN HADIS STUDI KASUS DI MI PESANTREN ANAK SHOLEH BAITUL QUR’AN GONTOR - Sugeng; Katni Katni; Riyanto; Nurul Iman; Tyas Ayuningrum (AL-MUADDIB: Jurnal Kajian Ilmu Kependidikan, 2023)
Currently there is a worrying character crisis in Indonesia. Facts prove it as news circulating on social media ranging from cases of students hitting teachers, bullying cases and so on. The objectives of this study are: 1) To explore and describe the strengthening of the character of students; 2) To analyze and describe the forms of Hadith learning in shaping the character of students; 3) To analyze and describe the implications of Hadith learning on the formation of the character of students. In this study, a descriptive qualitative research method will be used through a data mining process with stages of direct observation by researchers, interviews with several informants who are related to this study. The results of this study found that 1) Habituation through various activities at school; 2) Hadith Learning. While for Hadith Learning itself, it is done by dividing it into two stages (1) Learning in the classroom including a) Learning the Qur'an Hadith; b) Writing a Diary book with the theme of the Hadith that students have studied; c) A guidebook for memorizing students which is given by separating the theme of the Hadith; (2) Learning Hadith outside the classroom in the form of Muhadharah activities.